(untitled) (SAARC Journal of Agriculture, 2026)
This study was undertaken to investigate the stochastic impact of future climate conditions on the rice market and to identify the policy measures for poverty reduction in Bangladesh. Using of supply and demand structure of Bangladesh and secondary data collected from various published and online sources. The study period is divided into two periods where the first period (1977-2010) is taken for the parameter’s estimation of reference model and the second period (2011-2030) for comprehensive investigation of stochastic impact. To capture the probabilistic nature of climate variability, a random variable method and the inverse function of the cumulative standard normal distribution were applied. After big set of calibration, a percentile group by 90th and another group by 10th percentiles were set as upper and lower boundary to compare with the calibrated model output. Under stochastic climate impacts, rice yield variations ranged from 0.41 ton/ha to 1.78 ton/ha across the three major rice-growing seasons, clearly indicating the potential effects of climate shocks on future rice production. It undeniably clarifies the stochastic impact of climate shock on rice production in the future. Stochastic shock of climate increases the variation of rice price up to 33% in 2020, which may increase the vulnerable people by 25% through food expenditure increase. Such price instability will elevate food policy concerns through upward pressure on rice prices. Therefore, policymakers and economic policy interventions will play a crucial role in mitigating the stochastic impacts of climate shocks on the rice market. SAARC J. Agric., 23(2): 119-143 (2025)